Food quantity–quality interactions and their impact on consumer behavior and trophic transfer. Issue 1 (27th December 2019) - Burian, Alfred; Nielsen, Jens M.; Winder, Monika
Abstract: Food quantity–quality interactions determine growth rates and reproductive success of consumers and thereby regulate community dynamics and food web structure. Predator–prey models that shape our conceptual understanding of foraging ecology typically rely on the parametrization of fixed consumer responses to either food quantity or food quality. In nature, however, consumers optimize their fitness by responding simultaneously to changes in food quantity and quality. Therefore, we assessed consumer responses to changing food environments using a new fitness optimization model that accounted for food quality–quantity interactions to better capture the regulatory flexibility of consumers. Our simulations demonstrated that the impact of food quality on important consumer traits can be altered or even reversed by changes in food quality. Low food quality, for example, affected feeding rates negatively at low food concentrations but triggered surplus feeding at high food concentrations. The scope of surplus feeding was thereby mainly dependent on dynamics of nutrient digestion and in contrast to previous assumptions, energy costs of feeding played a minor role. Further, the regulation of digestive enzyme production, a crucial factor determining assimilation efficiencies, was strongly dependent on whether nonessential or essential nutrients were limiting growth. Consequently, not only the degree but also the type of nutrient limitation mediated the impact of the food environment on consumers' fitness. At the community level, food quality was key in shaping predator–prey biomass ratios. High food qualities resulted in top‐heavy systems with larger consumer than prey biomass. Decreases of prey digestibility or the availability of essential nutrients, however, triggered a switch from inverted to classical pyramid shapes of bi‐trophic systems. The impact of food quantity on trophic transfer and emerging structural ecosystem properties thus critically hinges on behavioral and physiological responses of consumers. The inclusion of the regulatory flexibility of consumers is therefore an essential next step to improve predator–prey models and our conceptual understanding of trophic interactions.